The Influence of Social Media Promotion on Online Purchase Decisions for Beauty Products - Naibaho, Lamtio Dame Lorita Br; Sianturi, Charles M.; Rajagukguk, Jonson (Golden Ratio of Data in Summary, 2024)
In the contemporary digital age, the internet has emerged as a powerful medium for product promotion, significantly influencing how people access information and fulfill their daily needs. This ease of access extends to business transactions, where entrepreneurs leverage the internet as a platform for online product sales. Social media, a relatively new mode of communication enabled by the internet, plays a pivotal role in this process. This research seeks to examine the impact of social media promotion on online purchasing decisions for beauty products among students at Universitas HKBP Nommensen, Medan.  The study employs a quantitative approach. The population consists of all students at Universitas HKBP Nommensen who have purchased beauty products online; however, the exact population size is not known. Using the Slovin formula, a sample of 100 respondents was randomly selected to represent each faculty. The findings reveal that social media promotion has a significant effect on purchasing decisions, as demonstrated by the results of the t-test. The t-value obtained was 8.429, exceeding the critical t-value of 1.4355, with a significance level of 0.000, which is less than the 0.05 threshold. The coefficient of determination (R²) was calculated to be 0.420, indicating that 42.0% of the variance in purchasing decisions can be attributed to social media promotion, while the remaining 58.0% is influenced by other factors not covered in this study. In conclusion, the research confirms that social media promotion has a positive and significant impact on the online purchasing decisions of beauty products among students at Universitas HKBP Nommensen, Medan.